Rapid detection of Atlantic salmon multi‐quality based on impedance properties. Issue 2 (21st January 2020) - Sun, Zongbao; Liang, Liming; Li, Junkui; Liu, Xiaoyu; Sun, Jian; Zou, Xiaobo; Zuo, Min; Guo, Zhiming
Abstract: To establish a rapid, convenient, and low‐cost method to assess the quality of Atlantic salmon, we analyzed the impedance between 10 –1 and 10 5  Hz for Atlantic salmon/rainbow trout, chilled/frozen‐thawed salmon, and fresh/stale salmon. We combined chemometrics with impedance properties to create a multi‐quality index for Atlantic salmon. The accuracy of all three models established can reach 100% in distinguishing Atlantic salmon from rainbow trout and distinguishing chilled salmon from frozen‐thawed salmon. We applied a partial least squares method to create a quantitative prediction model of bioimpedance spectroscopy and the value of total volatile basic nitrogen. The correlation coefficients of the training and test sets were 0.9447 and 0.9387. Our results showed that the combination of impedance properties and chemometrics was a simple and effective application to evaluate Atlantic salmon quality. Abstract : We established a multi‐quality rapid detection method to detect different quality Atlantic salmon by combining chemometrics with impedance properties. And the characteristics of bioimpedance spectra of salmon with different qualities were analyzed theoretically.